Application of Exponential Smoothing Method for Forecasting Clothing Sales at Ria Clothing Stores - Fiahati Laia; Hasanul Fahmi (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
Forecasting is one of the methods in data mining that can be used as the most important tool in effective planning, especially in the economic field. Forecasting the right product sales will be realized if a plan and analysis are made to determine how much sales volume must be achieved. Ria Busana is having problems not being able to increase profits and experiencing excess or shortage of inventory. In addition, sales data processing uses a manual system, resulting in sales continuing to experience losses. One of the forecasting methods based on time series cycles is to use the Exponential Smoothing method, this method is a continuous improvement procedure for forecasting new objects of observation by focusing on lowering a higher priority for forecasting than older observations.